Cell, Stephen King and the Imperial Gothic. Issue 2 (1st November 2015) - Unknown
Abstract : This essay argues that Stephen King's 2006 novel Cell explores the age of terror with the aid of two concurrent Gothic discourses. The first such discourse belongs to the tradition that Patrick Brantlinger has termed Imperial Gothic. As such, it imagines with the War on Terror that the threat that the (Gothic) Other constitutes is most usefully managed with the help of massive, military violence. The other, and more traditional, Gothic discourse radically imagines such violence as instead a War of Terror. The essay then argues that Cell does not attempt to reconcile these opposed positions to terror. Instead, the novel employs the two Gothic discourses to describe the epistemological rift that terror inevitably creates.